Joint meeting of I.F.T.U. Executive and L.S.I. Bureau, held in C.G.T. offices, Paris, on September 13th, 15th and 16th, 1937 (report) - International Federation of Trade Unions ; Labour and Socialist International
1937-09-20 016b-0050-002 292/946/16b/54(ii)